Optimizing The Effects of Auxin and Cytokinin Combinations on Shoot and Root Induction of Dendrobium mussauense - Noli, Zozy Aneloi; Nur, Fauziah; Suwirmen (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2024)
Dendrobium mussaense, an orchid species of high ornamental value, was subjected to experimental treatments involving the addition of combinations of auxin and cytokinin, namely 2,4-D (2,4-dichlorophenoxyacetic acid) with BAP (6-benzylaminopurine) and 2,4-D with TDZ (thidiazuron). The research aim was to evaluate their effects on the emergence time of shoots and roots. The method used an experiment design with seven treatments. Among the treatments, the most effective was 2,4-D at a concentration of 1 mg/L combined with 0.75 mg/L of BAP. This treatment resulted in the shortest time for both shoot and root emergence. These findings underscore the importance of optimizing hormone combinations for efficient shoot and root induction in D. mussaense, providing valuable insights for orchid propagation and cultivation practices.